Pengaruh rasio likuiditas, leverage, aktivitas, dan profitabilitas terhadap return saham (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
This research is conducted to find out the Influence of Liquidity, Leverage, Activity, and Profitability Ratio to Stock Return. The object of this research is Property and Real Estate Sector that listed in Indonesian Stock Exchange. The ratio that used in this research are liquidity with the indicator is Current Ratio (CR), leverage with the indicator is Debt to Equity Ratio (DER), activity with the indicator is Total Assets Turnover (TATO) and profitability with the indicator is Return On Equity (ROE). The data used in this research are kind of secondary data that colllected by documentation and library reserach method. The data sources are financial report of companies and the sample from 33 companies were selected by purposive sampling method. The analytic technique used in this research is multiple linier regression with SPSS aplication. The results of this research show that Current Ratio (CR) and Debt to Equity Ratio (DER) have an unsignifcantly negative influence to the stock return, on the other hand Total Assets Turnover (TATO) has a significantly positive influence to the stock return, and Return On Equity (ROE) has an unsignificantly positive influence to the stock return.